Development of Learning Media for Introductory Information and Communication Technology Courses - Mahmud Mustapa; Ummiati Rahmah; Muh. Asjart (Ceddi Journal of Education, 2022)
This research aims at: (1) finding out the learning conditions in Introduction to Technology of Information and Communication course of Electrical Engineering Education Department at Makassar State University; (2) finding out the developmental phases of learning media based on web learning in Introduction to Technology of Information and Communication course of Electrical Engineering Education at Makassar State University; and (3) finding out the validity level of learning media based on material and media experts' assessment. This research employed a developmental research using ADDIE which is modified in three phases that is Analyze, Design, and Develop. The research is conducted at Electrical Engineering Education Department at Makassar State University. The informants were chosen from material and media experts. In line with that, the data was obtained through observation and questionnaires, while technique of data analysis through descriptive analysis. The results of this study show three developmental phases of learning media based on web learning in Introduction to Technology of Information and Communication course of Electrical Engineering Education Department at Universitas Negeri Makassar as follows: (1) analyze phase; (2) design phase; and (3) develop phase. The results of the validator (1) validation by material experts achieving the feasibility of 82.81%, (2) by the design experts who reached 89.58% from the results of the study of learning media in Introduction to Technology of Information and Communication that are developing Electronics so as to produce excellent results for this company. The conclusion is that this research uses Research and Development (R&D).